Organization of the cross-border marketing center: functions, tasks and areas of activity - Kyfyak, Oleksandr (Herald of Economics, 2024)
Introduction. In the context of restoring the economic potential of each region, creating new jobs and solving a number of social problems, the need for innovation-oriented development of the economy on the basis of marketing has increased. For the border territories, where cross-border cooperation is established and international partnership relations exist, there is an urgent need to create a single network space, form and develop special economic zones, organize technoparks and incubators in the field of high technologies, use the capabilities of information systems, etc. The creation of a cross- border marketing center will contribute to solving these and other tasks of the regional economy on both sides of the border. Purpose. The purpose of the research is to study the possibilities of the organization of a cross-border marketing center, to determine its essence, tasks, functions, directions of activity, taking into account the main differences of the border regions of neighboring countries. Research methods. The methodological basis of the research was the study of foreign experience, the use of methods of analysis and synthesis, surveys, comparisons, expert assessments, etc. Research results. The article theoretically substantiates the expediency of creating a cross-border marketing center, taking into account international experience and expert assessments of specialists of the Chernivtsi Chamber of Commerce and Industry. The analysis of the markets of the border regions of Ukraine, Romania and Moldova contributed to the determination of the main directions of activity and tasks of the cross-border marketing center and allowed to establish the economic, territorial and cultural differences of the border regions of neighboring countries, which is an important prerequisite for the successful functioning of the cross-border marketing center. Based on a survey of enterprise managers of the Chernivtsi region, the main functions of the center were determined. Approaches to determining the effectiveness of cross-border marketing center functioning are proposed. Practical meaning. The formation of the cross-border marketing center was supported by entrepreneurs of the region. The organization of its practical activities with the assistance of the Chernivtsi Chamber of Commerce and Industry can be implemented in the shortest possible time. Prospects for further research. Important areas of further scientific research are the issues of organizational and legal support and financing of cross-border marketing center activities, solving personnel and infrastructure problems.